2021
DOI: 10.3390/su13042403
|View full text |Cite
|
Sign up to set email alerts
|

Green Water from Green Roofs—The Ecological and Economic Effects

Abstract: Green roofs (GRs) have been one of the most popular solutions for water harvesting in urban areas. Apart from their water retention role and increasing biodiversity, they constitute the missing link between the built and the natural environment, which is required for sustainable human living in cities. This paper aims to calculate the ecological (EE) and economic effect (EcE) of water harvesting via GRs, by contrasting with a traditional roof, and to perform an economic analysis of the social cost benefits tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 43 publications
(26 reference statements)
1
19
0
Order By: Relevance
“…The knowledge is very fragmented and scattered. Only a few papers by different authors contain topics on this issue [69][70][71][72]. However, some sources suggest that Warsaw is not a leader in promoting this type of solution [73].…”
Section: Sustainable Drainage Systems (Suds) and Water-sensitive Urba...mentioning
confidence: 99%
See 1 more Smart Citation
“…The knowledge is very fragmented and scattered. Only a few papers by different authors contain topics on this issue [69][70][71][72]. However, some sources suggest that Warsaw is not a leader in promoting this type of solution [73].…”
Section: Sustainable Drainage Systems (Suds) and Water-sensitive Urba...mentioning
confidence: 99%
“…In the context of specific scientific work, mention should be made, for example, of the study by Bus and Szel ągowska [72], who presented concrete calculations of the ecological and economic benefits of water retention by green roofs and carried out an analysis of the social-cost benefits for the entire life-cycle of green roofs. Their results showed that water retention and measurable environmental and economic benefits are the highest in cities such as Warsaw, Kraków and Wrocław, as these cities have the highest number of green roofs.…”
Section: Sustainable Drainage Systems (Suds) and Water-sensitive Urba...mentioning
confidence: 99%
“…In the case of the utilization of roofs, the benefits multiply, with the multiple services of green roofs to the sustainability of the urban environment, such as storm water management, reduction of urban heat island effects, noise reduction, and building temperature regulation, as well as connection between the built and the natural environment and direct contact of building occupants with the green roof with social and educational benefits [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Water treatment, water storage and retention areas are more efficient and economical on a larger scale [11,26,27]. Green roofs also become more economically and ecologically cost-effective in terms of rainwater management if they are implemented comprehensively [28]. In context of water flows, industrial processes, which often have significant water consumption, should also be considered [29].…”
Section: Discussionmentioning
confidence: 99%